Fatores associados à morbidade grave e Near Miss materno em centro terciário de atenção à saúde materna e neonatal - Lima, Hesly Martins Pereira (2016)
A pregnancy can be composed of a range of clinical conditions, ranging from a healthy pregnancy to another limit that is maternal death. Between these two extremes are the conditions described as severe maternal morbidity and near miss, which is a more severe condition than the maternal morbidity. In 2009, the WHO standardized maternal near miss approach, as an important tool to uniformly identify cases and evaluate the quality of care for women with serious complications. It is worth emphasizing that women who fall into these situations share many characteristics with maternal deaths, but represent a rich source of details about the determinant factors of their maternal health condition, since they are alive. Participated in this research 941 women who had severe maternal morbidity criteria and/or near miss during the period of July 2009 to June 2010, at the Maternity School Assis Chateaubriand - UFC. They were identified 61 cases of maternal near miss and 880 of severe maternal morbidity non-near miss. The incidence of maternal morbidity non-near miss was 190.6 and near miss was 10.8/1,000 live births. The mortality rate of maternal near miss was 18%. The variables significantly different between the two groups were: color (p = 0.002) and number of prenatal visits (p <0.001). Among the severe maternal morbidity conditions, it was found that eclampsia and the need for ICU admission were the defining of the risk of progressing to death, while the use of magnesium sulfate acted as a protective factor. It was found, also, that have criteria of near miss is statistically significant for maternal death (p <0.001; ORB = 3.94; 95% CI: 1.66 - 9.37). Among the defining criteria of near miss, the more directly associated with maternal death was the presence of management criteria: all the 11 cases that resulted in death had some management discretion. It was concluded that based health policies and actions in cases of maternal near miss is the most effective means of improving maternal health.